Nicole Oresme, Questiones in Meteorologica de ultima lectura, recensio parisiensis Study of the Manuscript Tradition and Critical Edition of Books I-II.10 - Panzica, Aurora (Medieval and Early Modern Philosophy and Science, 2021)
Nicole Oresme was one of the most original and influential thinkers of the fourteenth century. He is best known for his mathematical discoveries, his economic theories, as well as his vernacular translations of cosmological and ethical texts that were undertaken at the request of King Charles V. This volume sheds light on the beginning of Oresme's scientific activity at the University of Paris (ca. 1340 - ca. 1350), a period of his intellectual career about which little is known. Over the course of this decade, Oresme lectured on many Aristotelian texts on natural philosophy, such as the Physics, On the Heavens, On generation and corruption, Meteorology, and On the Soul. Oresme's commentaries on Aristotle's Meteorology count among his only unpublished texts. This volume presents the first critical edition of books I-II.10 of the second redaction of Oresme's Questions on Meteorology. The edition is preceded by a historical and philological introduction that discusses the context of Oresme's scientific career and examines the manuscript tradition. Readership: All interested in the history of Medieval Philosophy and in the reception of Aristotle's Meteorology in the Latin West.